A Pedestrian Navigation System Using Cellular Phone Video-Conferencing Functions. (31st December 2012) - Sugiura, Akihiko; Shoji, Takuya
Abstract : A user's position-specific field has been developed using the Global Positioning System (GPS) technology. To determine the position using cellular phones, a device was developed, in which a pedestrian navigation unit carries the GPS. However, GPS cannot specify a position in a subterranean environment or indoors, which is beyond the reach of transmitted signals. In addition, the position-specification precision of GPS, that is, its resolution, is on the order of several meters, which is deemed insufficient for pedestrians. In this study, we proposed and evaluated a technique for locating a user's 3D position by setting up a marker in the navigation space detected in the image of a cellular phone. By experiment, we verified the effectiveness and accuracy of the proposed method. Additionally, we improved the positional precision because we measured the position distance using numerous markers.